A new Sobralia (Orchidaceae: Sobralieae) from Panama - Serracín, Zuleika; Samudio, Zabdy; Bogarín, Diego (Phytotaxa, 2022)
In Panama, the Orchidaceae comprise 187 genera, of which one of the most conspicuous is Sobralia. The flowers of Sobralia are mostly ephemeral but colorful, often fragrant, and of variable sizes. Despite being a prominent group, its taxonomy is still underdeveloped in most neotropical countries. To continue with taxonomic studies in the Orchidaceae of Panama, we investigated a species of Sobralia, which differs from any recorded species of the genus. We documented the species with digital images and compared it with morphologically similar taxa. This paper describes and illustrates a new Sobralia from the Bosque Protector Palo Seco in the Fortuna area, Panama. Sobralia rinconiana differs from all other species recorded in Panama by the combination of a large plant size that reaches up to 120 cm high and the larger and broader, elliptical-lanceolate leaves (30–35 × 14–16 cm). Sobralia rinconiana is most similar to S. carazoi but differs in the spreading flowers with reflexed petals and the infundibuliform, cream-yellow lip, the wider, longer sepals and petals, and the longer, suberect column. The accurate estimate of the number of Sobralia species in Panama is still uncertain. Its diversity may increase as new areas are explored or species complexes are resolved.